Художня специфіка сучасного уроку музичного мистецтва - Панасюк, Світлана Леонідівна; Panasyuk, Svitlana L. (Чернівецький національний університет ім. Ю. Федьковича, 2014)
Стаття присвячена уроку музичного мистецтва. Розкривається роль вчителя у формуванні оцінного ставлення учнів до музики, та музичної діяльності. The article deals with the peculiarities of the organizational technologies of the Musical Art lesson. It exposes the essence of the specifics of the modern lesson on the base of the literary sources. It substantiates the significance of the personal pedagogical social intercourse, which has its own peculiarities at the Musical Art lessons, and it’s artistic-pedagogical. The article exposes the versatility of specifics of the teacher’s activity as the composer, the producer of the Musical Art lesson and the initiator of the artistic pedagogical social intercourse between the participants.
Art Specifics of Modern Musical Lesson
Keywords: урок; музичне мистецтво